CURRENT RATIO, DEBT TO EQUITY RATIO DAN NET PROFIT MARGIN PADA NILAI PERUSAHAAN - Muzalifatul Makiyah; Mulia Rahmah (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
The aim of this research is to test the effect current ratio, debt to equity ratio and net profit margin on company value in subsector companie property and real estate listed in Indonesian Stock Exchange for the 2017-2021 period. This research uses a purposive sampling method In selecting the sample used, 30 were selected sample